Liver Cancer and Risk Factors in the MENA Region: Epidemiology and Temporal Trends Based on the 2019 Global Burden of Disease Data - Najla A. Lakkis MD, MPH; Nour M. Mokalled MD; Mona H. Osman MD, MPH, MBA; Umayya M. Musharrafieh MD; Mohammad Eljammal MD (Cancer Control)
Background Liver cancer (LivCa) is a growing concern in the MENA region, driven by diverse factors, including viral hepatitis, lifestyle-related risks, and other causes. Methods Utilizing GBD 2019 data, we assessed LivCa patterns, emphasizing chronic viral hepatitis, non-viral factors, and health care disparities across the MENA region. Results Rising LivCa rates, particularly related to chronic viral hepatitis, highlight the region’s health challenges. Lifestyle factors, such as obesity and diabetes, contribute significantly. Disparities in health care access and cancer registration hinder accurate assessments. Conclusion A comprehensive strategy is vital, encompassing vaccination promotion, health care enhancements, and lifestyle awareness. Urgent coordinated efforts are needed to address disparities, implement evidence-based interventions, and alleviate the escalating LivCa burden in the MENA region.